Chemical Profiles and In Vitro Cholinesterase Inhibitory Activities of the Flower Extracts of Cassia spectabilis - null Suciati; Erlinda R. Laili; Wiwied Ekasari; null Kuatman; Nitra Nuengchamnong; Nungruthai Suphrom (Advances in Pharmacological and Pharmaceutical Sciences)
Background. Cassia spectabilis is a flowering plant containing various metabolites that provide potential for pharmacological activities. The current study aimed to investigate the ethanolic and water extracts of C. spectabilis as cholinesterase inhibitor as one of the target treatments for Alzheimer’s disease. The chemical composition of the extracts was also studied to determine which components are responsible for the bioactivity. Methods. The cholinesterase inhibitory activity assay was carried out by the modified Ellman’s method against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). LC-MS/MS analysis was carried out to investigate the chemical profiles of the extracts, followed by a molecular networking study by GNPS. Results. Both extracts showed inhibition against AChE and BChE in a dose-dependent manner, with the higher potency exhibited by the ethanolic extract with IC50 values of 7.88 and 3.78 μg/mL. The chemical analysis and molecular networking study of the flower extracts revealed similarity between the ethanolic and water extracts. Piperidine alkaloids were identified in both extracts, while the sphingolipid compounds were found in the ethanolic extract. Conclusion. The water and ethanolic extracts of C. spectabilis flowers displayed potency for Alzheimer’s disease treatment. The presence of piperidine alkaloids in the extract may be responsible for the cholinesterase inhibitory activity. The higher potency of the ethanolic extract compared to the water extract is possibly due to the higher amount of piperidine alkaloids in the ethanolic extract. Further study is needed to quantify the concentration of alkaloids in the extracts.